An international survey on recognition and characterization of atrophic gastritis and intestinal metaplasia - Yip, Hon Chi; Uedo, Noriya; Chan, Shannon M.; Teoh, Anthony Yuen Bun; Wong, Simon Kin Hung; Chiu, Philip W.; Ng, Enders Kwok Wai (Endoscopy International Open, 2020)
Background and study aims Atrophic gastritis (AG) and intestinal metaplasia (IM) are premalignant conditions of gastric cancer and endoscopic recognition and characterization may help in stratifying the gastric cancer risk for screening and surveillance. However, there is currently lack of consensus in defining the severity of AG and IM. We aimed to conduct an international survey to understand the current practice of endoscopists worldwide.Methods An online survey was designed to collect data regarding participants’ practice in endoscopic assessment of AG & IM. A test using images was conducted to evaluate the difference in accuracy of characterization of AG & IM. Results From July to October 2017, 249 endoscopists responded to the survey. Around 70 % of participants received some form of training on recognition of AG & IM. There was significant variety in the training received across different continents. One hundred seventy-six participants (70 %) would document the presence of both AG and IM, but the classification systems used were inconsistent between endoscopists. Overall accuracy in diagnosis of AG & IM in the image test was 84.5 % and 80.7 % respectively. The diagnostic accuracy was significantly higher among Japanese and Korean endoscopists compared to the rest of the world. Conclusion Training regarding endoscopic recognition of AG & IM differs significantly in different parts of the world. The difference in diagnostic accuracy for these premalignant gastric conditions may also explain the discrepancy in the early cancer detection rates among different countries. A simple unified classification system may be beneficial for better stratification of cancer risks.